A transferência de propriedade do solo criado para o particular quando do pagamento da outorga onerosa do direito de construir - Escudero, Fernando (2023)
The land use in Brazil has historically occurred through the transformation of forests areas into plantation areas, and villages, which have turned into cities. In recent centuries, these cities have increasingly required multifamily occupations due to limitation of horizontal growth. The transformation of rural land into urban land through real state development required the land developer to donate areas for the construction of roads, green areas, and institutional areas. The transformation of urban land to fit more people created a need for more urban infrestructure, but there was no legislation to allow the government to collect funds from the developers to invest in urban infrastructure. Whitin this context, the Property Rights concept received new interpretation regarding the social function of the land, to obligate the owner to use the land to serve the city. In this cenario, the owners building rights is limited to the standard Floor Ratio Area – FAR. The construction above this limited FAR would be considered Space Adrift which is owned by the government or the People. So the landowner that wants to build the Space Adrift must pay the Building Rights Grant, what is legally considered a burden for the proprietor. This master’s thesis will discuss if the payment of the Building Rights Grant implies in the acquisition of the property of the Space Adrift or implies on a simple authorization to build the licensed construction. The relevance of this discussion relies on the transformation of the urban centers that already have a lot of tall buildings, where these ancient building give space for newer and taller buildings, because these areas, usually, has more urban infrastructure than suburbs. Once a building is bought by a private broker, the Space Adrift used to build this building belongs to the new owner of the building? Can this new owner demolish the existing building and raise a new building on this land with the same Floor Ratio Area? To answer these questions is due to analyse how far goes the Construction Rights bounded to the Property Rights, so we will be able to understand how the Space Adrift is created, to then discuss the legal nature of the Building Rights Grant payment, and only then find out if the Space Adrift is a right or a real state property